2017
DOI: 10.1016/j.actbio.2017.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the morphology and outgrowth of nerve and neuroglial cells: The effect of surface topography

Abstract: There is increasing evidence that physical cues, such as topography, can have a significant impact on the neural cell functions. With the aid of micro-and nanofabrication techniques, new types of cell culture platforms are developed and the effect of surface topography on the cells has been studied. The present review article aims at reviewing the existing body of literature reporting on the use of various topographies to study and control the morphology and functions of cells from nervous tissue, i.e. the neu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
166
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(177 citation statements)
references
References 127 publications
8
166
0
3
Order By: Relevance
“…Several investigations have evaluated the influence of topographic cues on neurite growth. The majority of these studies used microgrooves with depths ranging from 200 nm to 69 μm 57 . While the grooves used in previous studies usually have well-defined shapes, i.e., square cross section with sharp edges, the aligned polymer structures on our β-PVDF films are much less ordered and exhibit small heights (<50 nm, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several investigations have evaluated the influence of topographic cues on neurite growth. The majority of these studies used microgrooves with depths ranging from 200 nm to 69 μm 57 . While the grooves used in previous studies usually have well-defined shapes, i.e., square cross section with sharp edges, the aligned polymer structures on our β-PVDF films are much less ordered and exhibit small heights (<50 nm, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Contact guidance refers to the phenomenon where adherent cells react to material surfaces with different surface topographies . As the cytoskeleton plays a major role in cellular fate, it is important to determine the morphology of adherent cells on scaffolds . Our results revealed that the general morphologies of cardiomyoblasts were controlled by the laser‐ablated microscale groove direction on the hierarchically patterned fibrous scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…The stem-cell responses, including adhesion, morphology, proliferation, and differentiation to different continuous, discontinuous, andr andom roughness topographies are summarized in Ta bles 1, 2and 3, respectively.The classification of the topographies into continuous, discontinuousa nd random was introduced in our previous review paper. [50] Briefly,p rimaryc lassification categorizes the various deterministic pattern geometries into continuous and discontinuous. As econd classification divides further the continuous geometries into anisotropic and isotropic topographies.…”
Section: The Effect Of Topographical Cues On Neural Stem Cellsmentioning
confidence: 99%